Assessment of Periodontal Status among Premenopausal and Postmenopausal Women in Mosul City - Aisha A. Qasim; Karama MT Al - Nuaimy; Alhan Ahmed (College of Education for Pure Sciences, 2012)
ABSTRACT To increase the understanding of oral health factors associated with menopause women, this research sought to examine the oral hygiene including clinical parameters (DMFT, gingival, calculus, plaque and pocket depth indices) and physical parameters (flow rate and pH) to show changes in postmenopausal women in Mosul City center in relation to premenopausal women. The sample chosen included 123 women 47 premenopausal and 76 postmenopausal women in age range from 30 - 61 years old. Clinical examination was carried out to detected DMFT, gingival, calculus, plaque and pocket depth indices, also measures physical parameters about flow rate and pH of saliva for each women. There was significant changes in the clinical and physical parameters when compared with age 46 - 61 years old, at p< 0.05 and highly significant at p< 0.001. Oral health in pre and post menopausal women should be considered as a separate problem from oral diseases. The clinical picture may vary from a localized to generalized inflammation would be of interest to physiologists and endocrinologists and might also prove to be value to the practicing dentists.